Diagnostic Study of Depressive State Among University Students by Using Kazakh Version of Inventory of Depressive Scal (Journal of Educational Sciences, 2020)
Inventory of Depressive symptoms (Rush, 1996) is one of the most popular questionnaire used for clinical diagnostic and research. This article is devoted to adaptation and validization of Kazakh version of Inventory of Depressive symptoms (IDS) for using it in the following psychophysiological study. IDS constructed from 30 questions based on subjects self-report about their feelings. Participants were 504 (185 male, 319 female) volunteers’ students of Universities of Almaty and other volunteers from the local population. Inclusion criteria was requirement of high school graduation in Kazakh language. All participants were acknowledged with experiment goals with written information and signed informed consent form. Study was approved by the Ethics Committee of the Medical Faculty of the Al-Farabi Kazakh National University. IBM SPSS21 was used for statistical analyses of Cronbach’s alpha for each questionnaire scale. Results showed significant internal consistency of the Kazakh version of the IDS which allowed us to use this questionnaire in psychophysiological study. Inventory of Depressive symptoms(IDS) will be used for diagnostic purpose among university students. Key words: Emotion, Depression, Cronbach’s Alpha, questionnaire.